A study of isotope-effects in the high-resolution 195Pt NMR spectra of octahedral complexes of the type [PtCl6-n(OH)n]2-, n = 0-6, in water - Engelbrecht, Leon de Villiers (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.